Challenges for management in implementing reforms at the ministry level and in health and social service organizations in Finland - Vuokko Niiranen; Joakim Zitting; Sanna Laulainen (Administrative Sciences, 2019)
The Finnish health and social care sector is currently undergoing numerous reforms. These reforms involve novel demands regarding the role of steering, decision-making, and management in health and social services. This article sheds light on some of the critical factors encountered by decision-makers and managers when implementing reforms to change health and social services. The article investigates cooperation between the steering ministries and different dimensions of management in local health and social service organizations. Interview data from the ministries were studied through content analysis, and quantitative survey data were analyzed using mean values guided by the model of multidimensional management. The co-operation between different ministries has intensified while implementing different reforms, but functional and cultural boundaries between them persist. The management dimensions in changing health and social service organizations stress the role of managers as facilitators and enablers, highlighting the significance of caring for the human resource dimension as one of the managers' core tasks. The successful implementation of change should never be automatic. What emerges prominently is the skill essential to achieve cooperation which transcends the borders of both multiprofessional and traditional professional and administrative work both in ministries and local health and social service organizations.
Keywords: 350; managing reforms; strategic management; policy implementation; ministry collaboration; management dimensions; multidimensional management; health and social services